An In Situ Depot for Continuous Evolution of Gaseous H2 Mediated by a Magnesium Passivation/Activation Cycle for Treating Osteoarthritis. Issue 31 (6th July 2018) - Wan, Wei‐Lin; Lin, Yu‐Jung; Shih, Po‐Chien; Bow, Yu‐Ru; Cui, Qinghua; Chang, Yen; Chia, Wei‐Tso; Sung, Hsing‐Wen
Abstract: Inflammation is involved in many human pathologies, including osteoarthritis (OA). Hydrogen (H2 ) is known to have anti‐inflammatory effects; however, the bioavailability of directly administered H2 gas is typically poor. Herein, a local delivery system that can provide a high therapeutic concentration of gaseous H2 at inflamed tissues is proposed. The delivery system comprises poly(lactic‐co‐glycolic acid) microparticles that contain magnesium powder (Mg@PLGA MPs). Mg@PLGA MPs that are intra‐muscularly injected close to the OA knee in a mouse model can act as an in situ depot that can evolve gaseous H2 continuously, mediated by the cycle of passivation/activation of Mg in body fluids, at a concentration that exceeds its therapeutic threshold. The analytical data that are obtained in the biochemical and histological studies indicate that the proposed Mg@PLGA MPs can effectively mitigate tissue inflammation and prevent cartilage from destruction, arresting the progression of OA changes. Abstract : Upon intramuscular administration, water infiltrates the PLGA microparticles to react with their encapsulated Mg powders, evolving H2 bubbles and producing Mg(OH)2 on their surfaces, making them unreactive. The passivated Mg can then be activated by the chloride (Cl − ) ions in body fluids. The cycle of passivation/activation of Mg can thus evolve gaseous H2 continuously to the inflamed cartilage, arresting progression of osteoarthritis (OA).